Energy-Efficient TDMA based Clustering Scheme for WSN: Energy-Efficient TDMA based Clustering Scheme for WSN - Ahmad, Shakeel; Zafar, Mohammad Haseeb; Ashraf, Majid; Khan, Imran; Khan, Fazal Qudus (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
Wireless Sensor Networks (WSNs) are broadly deployed for civil and military purposes. WSN is a sensor network used to monitor physical and environmental conditions of a system such as a temperature, sound, and pressure. Sensors collect the data and send it to the desired destination such as base station. It consists of tiny nodes having very limited energy; once this energy ends then the node dies. Energy consumption is a major issue in these sensor networks. Hence, the focus of this research is to make these sensors cheap and energy-efficient. In order to gain optimized results, hundreds and thousands of nodes are deployed. To make the system more energy efficient, different routing techniques are used. In this paper, a new Efficient Time Division Multiple Access (TDMA)-based Clustering (ETC) Scheme for WSNs has been introduced which is more energy efficient than other schemes. ETC scheme uses clustering and TDMA by using hierarchy. In this hierarchy, nodes are divided into three levels, lower level nodes, medium level nodes and high energy nodes. Simulation results show that ETC has high energy efficiency, higher throughput and lower end-to-end delay. ETC results have been compared with existing schemes like Modified LowEnergy Adaptive Clusturing Hierarchy (MODLEACH) and Low-Energy Adaptive Clusturing Hierarchy (LEACH)CCH. ETC showed better results than these schemes. ETC was 2.13% better than Low-Energy Adaptive Clusturing Hierarchy -CCH and Modified Low-Energy Adaptive Clusturing Hierarchy in case of throughput analysis. ETC had less energy consumption than Low-Energy Adaptive Clusturing Hierarchy-CCH and Modified Low-Energy Adaptive Clusturing Hierarchy. ETC showed 2.29*104 joules of average energy consumption which was far better than LowEnergy Adaptive Clusturing Hierarchy-CCH which showed1.16*105 joules and Modified Low-Energy Adaptive Clusturing Hierarchywhich was 3.63*104 joules. In the end-to-end delay, ETC show much better results as compared to Low-Energy Adaptive Clusturing Hierarchy-CCH and Modified Low-Energy Adaptive Clusturing Hierarchy. ETC showed 4.94*104 seconds of an end-to-end delay which was far better than Low-Energy Adaptive Clusturing Hierarchy-CCH which shows 9*104 seconds and Modified Low-Energy Adaptive Clusturing Hierarchy which was 6.66*104 seconds. It is shown from the results that ETC has high stability period and higher throughput.